The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1371/journal.pntd.0005572
|View full text |Cite
|
Sign up to set email alerts
|

First-time detection and identification of the Mycobacterium tuberculosis Complex members in extrapulmonary tuberculosis clinical samples in south Tunisia by a single tube tetraplex real-time PCR assay

Abstract: IntroductionTunisia has one of the highest burdens of extrapulmonary tuberculosis (EPTB) among tuberculosis (TB) cases but the contribution of MTBC-mediated human EPTB is unknown. EPTB diagnosis is challenging due to the paucibacillary nature of clinical samples. Therefore, a need of a simplified molecular method for sensitive and specific TB detection and differentiation of MTBC members caused EPTB remains a priority to an early diagnosis, optimize successful anti-TB treatment and minimize transmission. We ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 24 publications
6
20
0
2
Order By: Relevance
“…On the other hand, DNA can be detected from non-cultivable or dead MTC bacteria for the cases treated [ 25 ]. Therefore, our study confirms that 1) the use of culture or the PCR alone cannot be a criterion to determine the negativity of the results and 2) a comparison with the clinical data is strongly necessary when making decisions during diagnosis [ 26 ]. Real-time PCR showed a high sensitivity (95.2%) and a good specificity (95.4%) on pulmonary samples, notice that the same rates were reported by other authors [ 14 , 27 ].…”
Section: Discussionsupporting
confidence: 63%
“…On the other hand, DNA can be detected from non-cultivable or dead MTC bacteria for the cases treated [ 25 ]. Therefore, our study confirms that 1) the use of culture or the PCR alone cannot be a criterion to determine the negativity of the results and 2) a comparison with the clinical data is strongly necessary when making decisions during diagnosis [ 26 ]. Real-time PCR showed a high sensitivity (95.2%) and a good specificity (95.4%) on pulmonary samples, notice that the same rates were reported by other authors [ 14 , 27 ].…”
Section: Discussionsupporting
confidence: 63%
“…In South Tunisia, almost 77% of clinically and bacteriologically diagnosed cases of EPTB are attributed to M . bovis [7]. To our knowledge, this is the first study that investigates molecular characterization of M .…”
Section: Discussionmentioning
confidence: 99%
“…In South Tunisia, Siala et al have detected M . bovis by qPCR in almost 77% of extrapulmonary samples taken from patients with EPTB [7]. In addition, LTB was estimated to be 50% of all EPTB cases of which cervical localization was the most frequent (70% to 90%) [5, 8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated that raw milk consumers are at high risk of being infected with M. bovis [ 30 ]. Numerous clinical cases of human extrapulmonary tuberculosis due to M. bovis have been recently documented in Tunisia [ 31 , 32 ] and the consumption of unpasteurized dairy products has been indicated as the most likely source of transmission [ 33 ]. Implementation of effective and comprehensive strategies to control bTB and to prevent zTB are therefore of primary importance in the country.…”
Section: Introductionmentioning
confidence: 99%